Perkembangan Kognitif dan Emosional Anak Usia 5 Tahun Melalui Gerak dan Lagu - Lati Nurliana Wati Fajzrina; Fatmawati Fatmawati; Munawarah Munawarah; Nur Cahyati Ngaisah; Arsyia Fajarrini; Devi Meilasari; Kiki Ayu Hermawati (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2023)
Based on the research, the problem is focused on how children's cognitive development and children's emotional development through the provision of stimuli with motion and song methods in children aged 5 years. The goal is, to find out the extent of development that occurs in children, especially in the cognitive and emotional aspects when using motion and song methods. The method used by the researcher is a phenomenological study based on events that occur in the field. The results of the research conducted found that the cognitive and emotional development of children was well stimulated using the motion and song methods applied to children. In addition, it also has a positive impact on other children's development such as language, social, artistic, kinesthetic, creativity, imagination, physical aspects as well as having an impact on body health which makes children more active and energetic.